2022
DOI: 10.1093/ageing/afac095
|View full text |Cite
|
Sign up to set email alerts
|

Mobility screening for fall prediction in the Canadian Longitudinal Study on Aging (CLSA): implications for fall prevention in the decade of healthy ageing

Abstract: Background Guidelines for fall prevention in older adults recommend mobility screening for fall risk assessment; however, there is no consensus on which test to use and at what cutoff. This study aimed to determine the accuracy and optimal cut-off values of commonly used mobility tests for predicting falls in the Canadian Longitudinal Study on Aging (CLSA). Methods Mobility tests at baseline included the Timed Up and Go (TUG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Our results showed that only low performance, as assessed by the TUG test time at baseline, was associated with a higher prevalence of falls. TUG is the most commonly used tool in studies assessing fall risk, precisely because it evaluates, in addition to walking ability, other dimensions such as balance and strength [ 22 ], while GS has shown inconsistent results for predicting falls [ 6 , 52 , 53 ]. The Canadian Longitudinal Study on Aging verified that neither of the commonly used PP tests (TUG and GS) achieved acceptable accuracy in identifying individuals with at least one fall at follow-up (18 months) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that only low performance, as assessed by the TUG test time at baseline, was associated with a higher prevalence of falls. TUG is the most commonly used tool in studies assessing fall risk, precisely because it evaluates, in addition to walking ability, other dimensions such as balance and strength [ 22 ], while GS has shown inconsistent results for predicting falls [ 6 , 52 , 53 ]. The Canadian Longitudinal Study on Aging verified that neither of the commonly used PP tests (TUG and GS) achieved acceptable accuracy in identifying individuals with at least one fall at follow-up (18 months) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…TUG is the most commonly used tool in studies assessing fall risk, precisely because it evaluates, in addition to walking ability, other dimensions such as balance and strength [ 22 ], while GS has shown inconsistent results for predicting falls [ 6 , 52 , 53 ]. The Canadian Longitudinal Study on Aging verified that neither of the commonly used PP tests (TUG and GS) achieved acceptable accuracy in identifying individuals with at least one fall at follow-up (18 months) [ 52 ]. This is in agreement with previous studies in which the values of sensitivity and specificity ranged from weak to moderate for the TUG and 4 m GS tests [ 28 , 29 , 30 , 33 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The time (in seconds) that they were able to balance on 1 foot before their foot touches the ground or they lose balance and touch the wall was recorded with a maximum time of 60 seconds. A cutoff based on previous work published with this data set was chosen to be 4.5 seconds (18); a time of 4.5 seconds or less indicates impaired balance. The TUG was used to assess mobility.…”
Section: Methodsmentioning
confidence: 99%
“…The time (in seconds) was recorded for how long it takes the participant to stand up from the chair, walk 3 meters, turn around, walk back to the chair and sit down again at their normal pace. A cutoff of 14.2 seconds was used (18); a time of 14.2 seconds or more indicates impaired mobility. The chair‐rise test assesses balance and coordination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation